Participation of Magnesium in the Secretion and Signaling Pathways of Insulin: an Updated Review - de Sousa Melo, Stéfany Rodrigues; dos Santos, Loanne Rocha; da Cunha Soares, Tamires; Cardoso, Bruna Emanuele Pereira; da Silva Dias, Thaline Milany; Morais, Jennifer Beatriz Silva; de Paiva Sousa, Mickael; de Sousa, Thayanne Gabryelle Visgueira; da Silva, Nilmara Cunha; da Silva, Lyandra Dias; Cruz, Kyria Jayanne Clímaco; do Nascimento Marreiro, Dilina (Biological trace element research, 2022)
Several studies have demonstrated the participation of various minerals in mechanisms involving insulin. Magnesium, in particular, plays an important role in the secretion and action of this hormone. Therefore, this review aimed to examine the latest insights into the biochemical and molecular aspects of the participation of magnesium in insulin sensitivity. Magnesium plays a vital role in the activity of intracellular proteins involved in insulin secretion in β-pancreatic cells, such as glucokinase, ATPase, and protein kinase C. In addition, evidence suggests that this mineral participates directly in insulin sensitivity and signaling in peripheral tissues, acting in the phosphorylation of the receptor tyrosine kinase and the insulin receptor substrates 1, insulin receptor substrates 2, phosphatidylinositol 3-kinase, and protein kinase B, and indirectly by reducing oxidative stress and chronic low-grade inflammation, which also lead to insulin resistance. Thus, magnesium deficiency is associated with glucose intolerance, while magnesium supplementation stimulates insulin secretion in pancreatic cells and improves insulin sensitivity in peripheral tissues. However, studies must consider assess short- and long-term nutritional status of mineral before performing intervention, the relevance of the balance of other nutrients that influence hormone secretion and sensibility, and health status of the assessed population.